WANPRESTASI PENGUSAHA PT. XENTRA GLOBAL INNOVATIVE ATAS KETERLAMBATAN PEMASANGAN PAPAN NAMA TOKO MILIK CV. BONANZA ESTETIKA DI KABUPATEN MELAWI - NIM. A1011161207, VINSENSIUS BOBIE DWIPAYANA (Fakultas Hukum Universitas Tanjungpura, 2023)
Abstrac The implementation of the agreement between the Employer of PT Xentra Global Innovative with CV Bonanza Aesthetics as a service user which in civil law is included in the type of agreement to perform certain services. The agreement between the Employer of PT Xentra Global Innovative and CV Bonanza Aesthetics is done orally (not written). Although it is done orally, its binding force is the same as an agreement made in writing and the agreement gives rise to rights and obligations for the parties, because the agreement has fulfilled the conditions for the validity of the agreement stipulated in Article 1320 of the Civil Code, namely agreeing those who bind themselves, the ability to make or say an agreement, a certain thing and a halal cause.This thesis according to the formulation of the problem: